Modularer Aufbau von Nachhaltigkeitsindikatorensystemen: Ein Ansatz zur Verbesserung der Wirksamkeit von Indikatorensystemen in der kommunalen Praxis - Heiland, Stefan; Tischer, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The present use of sustainability indicator systems in local communities in practice remains far behind the potentials claimed for them. As main reasons for that have been identified: many existing local sustainability indicator systems are designed to meet a variety of targets. Any specific requirements are neglected. Second, most local sustainability indicator systems are designed and applied outside the political and administrative structures and processes of a local community. Their integration into the local context until now has not received enough attention. Third, the differentiation of modern societies makes the implementation of integrated approaches difficult. As a reaction, in this paper a modular design for indicator systems, is suggested and outlined in its main features.